Utilization of Mixed Maggot Flour (Hermetia illucens) and Taro Leaves (Colocasia esculenta) for the Growth of Nile Tilapia (Oreochromis niloticus) - Alkausar, Triawan; Angelica, Mey Chika (WISE Pendidikan Indonesia, 2024)
Tilapia (Oreochromis niloticus) is a popular freshwater fish with promising development prospects due to its clean white flesh, high nutritional content, and affordability. However, feed costs in tilapia farming pose challenges, particularly with rising prices of fish meal, the primary protein source. Maggot (Hermetia illucens) and taro leaves (Colocasia esculenta) offer an alternative protein source for tilapia feed due to their high protein content. This study, conducted over 30 days in Marga Agung Village, South Lampung, tested the effects of different feed mixtures using a completely randomized design (RAL) with 4 treatments and 3 repetitions. The study involved 120 tilapia, evaluating parameters such as weight gain, specific growth rate (SGR), absolute length, feed conversion ratio (FCR), temperature, and pond clarity. Data analysis via ANOVA and Duncan's test showed the highest results in the control group (P0), with an average weight of 8.43g, an SGR of 28%, and an FCR of 1.42. Treatment P2 (50% maggot and 50% taro leaves) produced comparable results, with an average weight of 8.09g, an SGR of 27%, and an FCR of 1.44. Environmental conditions remained stable across treatments, with pH and water clarity showing minimal variation. These results suggest that a 50% maggot and 50% taro leaf mixture could be a viable alternative to fish meal for tilapia feed without significant differences in growth performance compared to the control.